Desain Strategi Peningkatan Daya Saing Industri Pengolahan Makanan Ringan Berbasis Klaster di Sumatera Barat - Insannul Kamil; Rika Ampuh Hadiguna; Berry Yuliandra; Aulia Rahman (Jurnal Optimasi Sistem Industri, 2016)
Food processing industries have grown in the region of West Sumatra since a few decades ago. The processing of various types of food recipes from various West Sumatra region comes from inheritance hereditary. Snack is a processed food product that has a special attraction among various types of distinctive food from West Sumatra. Increasing competitiveness is necessary to accelerate the growth of small and medium snacks industries in West Sumatera. Industrial cluster development is one of the strategic and effective approaches to achieve that objective. The research aims to design value chain and industrial cluster map model of small and medium snacks industries in West Sumatra. Industrial cluster mapping carried through: defining the value chain, a grouping of factors influence the level of internal and external factors, factors condition processing, grouping factor conditions into the four elements of SWOT, strategy planning using SWOT Matrix, and creating industrial cluster map of snacks industries in West Sumatra. The results showed that there are 7 internal factors and 6 external factors that can influence the competitiveness of small and medium snacks industries in West Sumatra. The value chain of snack industry in West Sumatra includes tuber farmers, traditional market, special suppliers, small and medium snacks industries, and consumers. The study also generates 10 programs centered on small and medium snacks industries in West Sumatra as a core industry.